2021
DOI: 10.3389/fenvs.2021.656271
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons and Potentially Toxic Elements in Soils of the Vicinity of the Bulgarian Antarctic Station “St. Kliment Ohridski” (Antarctic Peninsula)

Abstract: The investigation conducted was dialed to quantitative and qualitative evaluation of 15 priority polycyclic aromatic hydrocarbons (PAHs) and Potentially Toxic Elements (Cu, Pb, Zn, Cd, Ni, and Cr) is soils and cryoconites on “St. Kliment Ohridski” Antarctic station territory and its vicinities. Estimation of benzo(a)pyrene (BaP)–equivalents, PAHs and different PAHs isomer pair ratios were used for identification of general toxicity, nature and origin of individual PAHs and their groups. Total concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Local contamination is typical only for transport arteries and polar station sites [19]. The increased portion of zinc was documented for soils of polar station Kliment Orhidsky, Livingstone Island [48]; thus, our data confirmed these results.…”
Section: Features Of Trace Elements Accumulation In Cryoconite On The...supporting
confidence: 88%
See 2 more Smart Citations
“…Local contamination is typical only for transport arteries and polar station sites [19]. The increased portion of zinc was documented for soils of polar station Kliment Orhidsky, Livingstone Island [48]; thus, our data confirmed these results.…”
Section: Features Of Trace Elements Accumulation In Cryoconite On The...supporting
confidence: 88%
“…As a result of glacier retreat, cryoconite dust brought here via water currents is deposited on moraine sediments, which plays an important role in primary soil formation [4]. Cryoconite material is a significant source of carbon and nitrogen under conditions of poorly developed soil formation and serves as a catalyst for soil formation in areas freed from glaciers [34,48]. Soil formation could take centuries under conditions in which cryoconite dust did not enter moraine sediments, but if the cryoconite dust is contaminated with trace elements, the process could take even longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of benz[a]pyrene equivalents (BaPYR-equivalents) is the product of the PAH concentration by its toxic equivalency factor (TEF); the values of these factors are published by Nisbet [35]. The possibility of calculating these factors for the Antarctica soils was explained in the work earlier [36].…”
Section: Methodsmentioning
confidence: 99%
“…They found that phenanthrene accounted for a high proportion, with concentrations ranging from 1.95 to 42.18 ng/g, representing 24–50% of the total PAHs. The concentrations of PAHs in soil from the vicinity of the Bulgarian Antarctic Station (St. Kliment Ohridski) were studied by Abakumov et al 9 . In these works, the concentration of PAHs in soils ranged from 170 to 200 μg/kg.…”
Section: Introductionmentioning
confidence: 99%